ICT and Productivity in Developing Countries: New Firm-Level Evidence from Brazil and India - Commander, Simon; Harrison, Rupert; Menezes-Filho, Naercio (The Review of Economics and Statistics, 2011)
This paper uses a unique new data set on manufacturing firms in Brazil and India to estimate production functions, augmented by information and communications technology (ICT). We find a strong positive association between ICT capital and productivity in both countries that is robust to several different specification tests. The paper also breaks new ground when using the Indian data to investigate the effect of the institutional and policy environment on ICT capital investment and productivity. We find that poorer infrastructure quality and labor market policy are associated with lower levels of ICT adoption, while poorer infrastructure is also associated with lower returns to investment.